Home and the limits of belonging: Homophobia and return migration to Peru. (September 2019) - Alcalde, M Cristina
This article examines how in Peru LGB experiences of return migration expose multiple forms of exclusionary incorporation that mark the home—in terms of family, city, and nation—as a site of simultaneous safety and fear. I suggest that Peruvian return migrants who identify as lesbian, gay, and bisexual find themselves in the difficult and dangerous position of experiencing violence against them—homophobic practices, jokes, silencing, and discrimination—in order to be at home with their families, and in the city post-return. These forms of post-return violence exclude them even as they are otherwise seemingly incorporated back into their families and communities.